Biondication of Anthropogenic Load on Agrobiodiversity in the Northern Azov Region of Ukraine - Fedyushko, M. P.; Fedyushko, Y. M.; Kovalenko, D. V. (Man and Environment. Issues of Neoecology, 2020)
Purpose. Determination of informative value of types of bioindicators from a number hunting animals for the estimation of the ecological state of agricultural landscapes and level of transformation in them of biological variety.Methods. The field (noise tuning-up, rout); ecological-analytical, statistical, methods of matrix algebra. Results. It is set that in the conditions of Northern Azov region of Ukraine by key anthropogenic factors that determine the quantity of population : for a partridge grey is a structure of agricultural landscapes; for the European hare-hare - structure of sowing areas, quantity of predators and state of sunny activity. Considerable cross-correlation connection is first set between the quantity of populations of indicatory kinds and pesticide loading on territory as on regional, so on local levels. In the dynamics of populations of indicatory kinds found out the short and long waves of quantity. In the conditions of the pesticide pressure the most vulnerable is regulative influence of zoophages on consumers of more subzero orders. Therefore at megascopic pesticide loading regulative influence of predators will diminish on the row of representatives of phytophages, that explains the phenomenon of increase of quantity of some phytophages at general toxic impact from pesticides. Conclusions. A high closeness of population and thick infrastructural network are the substantial factors of transformation of biovariety within the limits of region. The general of biological variety in a region as very tense. The ecological ground of potential kinds-indicators allows on the basis of investigational conformities to law the dynamics of their populations of different level of spatial organization to offer the method of bioindication of ecological violations in agricultural landscapes. Thus the informing index of anthropogenic pressure is a current quantity of population of indicatory type of the field fowl.